2020
DOI: 10.3390/ijerph17114145
|View full text |Cite
|
Sign up to set email alerts
|

Source Apportionment of Coarse Particulate Matter (PM10) in Yangon, Myanmar

Abstract: The Republic of the Union of Myanmar is one of many developing countries facing concerns about particulate matter (PM). Previously, a preliminary study of PM2.5 in 2018 suggested that the main source of PM in Yangon, the former capital, was vehicle emissions. However, this suggestion was not supported by any chemical composition data. In this study, to fill that gap, we quantitatively determined source contributions to coarse particulate matter (PM10) in Yangon, Myanmar. PM10 samples were collected in Yangon f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Southeast Asia (SEA) is strongly affected by atmospheric haze pollution (Wiriya et al, 2013;(Li and Shao, 2009;Pongpiachan et al, 2014a;Pongpiachan et al, 2015;Chuang et al, 2016;Li et al, 2016;Chomanee et al, 2020;Dejchanchaiwong et al, 2020;ChooChuay et al, 2020a;ChooChuay et al, 2020b;ChooChuay et al, 2020c;Dejchanchaiwong and Tekasakul, 2021). In the upper SEA, the haze is observed during a quarter of every year and studied, mostly in Thailand (Wiriya et al, 2013;Wiriya et al, 2016;Thepnuan et al, 2019;Pani et al, 2019), but recently, air quality affected by PM10 and PM2.5 was studied in Laos (Nguyen et al, 2019), Myanmar (Sricharoenvech et al, 2020) and Vietnam (Le, 2020). Previous investigations showed that aerosol particles in northern Thailand originated from biomass burning both transboundary and domestic sources (Wiriya et al, 2013).…”
Section: Accepted Manuscript 1 Introductionmentioning
confidence: 99%
“…Southeast Asia (SEA) is strongly affected by atmospheric haze pollution (Wiriya et al, 2013;(Li and Shao, 2009;Pongpiachan et al, 2014a;Pongpiachan et al, 2015;Chuang et al, 2016;Li et al, 2016;Chomanee et al, 2020;Dejchanchaiwong et al, 2020;ChooChuay et al, 2020a;ChooChuay et al, 2020b;ChooChuay et al, 2020c;Dejchanchaiwong and Tekasakul, 2021). In the upper SEA, the haze is observed during a quarter of every year and studied, mostly in Thailand (Wiriya et al, 2013;Wiriya et al, 2016;Thepnuan et al, 2019;Pani et al, 2019), but recently, air quality affected by PM10 and PM2.5 was studied in Laos (Nguyen et al, 2019), Myanmar (Sricharoenvech et al, 2020) and Vietnam (Le, 2020). Previous investigations showed that aerosol particles in northern Thailand originated from biomass burning both transboundary and domestic sources (Wiriya et al, 2013).…”
Section: Accepted Manuscript 1 Introductionmentioning
confidence: 99%
“…Southwest wind prevails during this area's rainy season (May-October) (https://weatherspark.com/y/112503/Average-Weather-in-Yangon-Myanmar-(Burma)-Year-Round). Hence, we assumed that rice plants in the sites grew without exposure to the Yangon urban area's aeolian dust, 5.2% of roadway emissions [71]. Many countries have reported high Pb contents in roadside soils [72].…”
Section: Lead Contents In Rice Grains From the Worldmentioning
confidence: 99%
“…These compounds could be oxidation products from Vončina: Marker Compounds Adsorbed on Dust Particles ... biopolymers or incomplete combustion product, and they could represent secondary organic compounds formed by photochemical reactions. 10,11 The presence of n-alkanes and a fraction of polycyclic aromatic compounds (PAH) is low, at detection limit of the experimental method. It is related to the summer season, when there is no use of fossil fuels for heating and at the same time the photochemical degradation is high.…”
Section: Influences Of the Urbane Background Atmospherementioning
confidence: 99%